The Effect of Inorganic Preservatives in the Norway Spruce Wood on Its Wettability and Adhesion with PUR Glue - Dávid Ciglian; Ladislav Reinprecht (Applied Sciences, 2022)
Recycled recovered wood, for example, from historic buildings, containing biocides, fire retardants or anti-weather paints is an attractive material for manufacturing composite wood panels which can be used for decoration as well as load-bearing walls with a typical patina. This paper investigates the effect of four inorganic wood preservatives—CuSO4·5H2O, ZnCl2, H3BO3 and (NH4)2SO4—commonly used in the past, with the focus on their effect on the quality of wood bonding. The milled surfaces of Norway spruce (Picea abies Karst L.) wood were treated with 0.5, 1 and 2% aqueous solutions of these preservatives. The effect of preservatives in spruce wood was evaluated: (1) by its wettability with the drops of redistilled water, measuring the contact angles; (2) by the shear strength of the “spruce wood—polyurethane (PUR) Kestopur 1030 glue” interphases according to the standard EN 205; (3) by microscopic analysis of the “wood—PUR” interphases. The wettability of spruce wood worsened when using ZnCl2, by a maximum of 28.2%, but on the contrary, it improved due to other preservatives mainly by using (NH4)2SO4, at a maximum of 22.9%. In general, the shear strength of glued joints “wood—PUR” continually decreased with higher concentrations of all the preservatives. The most significant decrease of adhesion “wood—PUR”, by 19.8% from 10.66 MPa to 8.55 MPa, was caused by 2% ZnCl2 used for the treatment of both spruce wood specimens in interphase with the PUR glue. On the contrary, the less significant decrease of adhesion “wood—PUR”, by 2.5%, was caused by 0.5% (NH4)2SO4 applied only on one surface of the two inter-bonded spruce wood specimens. The effects of preservatives on the wood wettability and its adhesion with PUR glue were partly confirmed by microscopic analysis.